BBC Micro:bit in practice a hands-on guide to building creative real-life projects with MicroPython and the BBC Micro:bit - Pajankar, Ashwin; Sharma, Abhishek; Saini, Sandeep (Packt Publishing Limited, 2022)
Develop real-world interactive physical computing applications using the Micro:bit with more than 100 MicroPython examples with circuit diagrams Key Features Explore hardware programming and leverage the power of the BBC Micro:bit and MicroPython Build real-life creative projects step by step with each chapter increasing in complexity and interactivity Learn the features of the Micro:bit and how to interface it with electronic components through circuits and code examples Book Description This book is a one-stop guide for learning BBC Micro:bit with MicroPython, exploring many hardware components and programming techniques to provide detailed insights into developing practical applications with the Micro:bit. It will also show you how hardware components can be manipulated using a combination of Micro:bit and MicroPython for developing practical projects.
Keywords: Mikrocontroller